SOCIOCULTURAL AND PSYCHOLOGICAL INFLUENCES ON PREMARITAL SEXUAL BEHAVIOR AMONG NIGERIAN UNIVERSITY STUDENTS - Uwakwe , Chinedu Emmanuel (International Research Journal of Sociology, Psychology and Anthropology, 2025)
Adolescent sexual behavior has become a growing concern worldwide, with increasing premarital sexual activities observed in various regions, particularly Sub-Saharan Africa. Studies have highlighted a concerning rise in sexual activity among adolescents, often coupled with limited knowledge about sexual and reproductive health. In many developing countries, youth are often unable to openly discuss sexual matters due to cultural taboos and social stigmas. Consequently, young people frequently rely on peers for information, which may be inadequate or misleading. Research indicates that adolescents possess limited understanding of puberty, sexual health, and contraception, increasing their vulnerability to sexual health risks, including unintended pregnancies and sexually transmitted infections (STIs). This issue is further exacerbated in the context of the HIV/AIDS pandemic, which disproportionately affects young people, particularly adolescents. The lack of accurate sexual education and the stigma surrounding sexual discussions contribute to the ongoing health challenges faced by youth. This paper aims to explore the implications of inadequate sexual education among adolescents, focusing on the challenges of accessing reliable information and the potential health risks associated with ignorance about reproductive health. By understanding the gaps in sexual education and the impact of cultural factors, this study seeks to highlight the urgent need for comprehensive sexual and reproductive health education tailored to adolescents, to reduce risks and promote healthier sexual behaviors